Orthodontic management of patient with cleft lip and palate: Penanganan ortodontik pada penderita celah bibir dan lelangit - Andi Kurniati; Ardiansyah S. Pawinru; Baharuddin M. Ranggang (Makassar Dental Journal PDGI Makassar, 2024)
Patients with cleft lip and palate have complex disorders and require long-term care. The treatment of CLP requires orthodontic and surgical treatment as well as an interdisciplinary approach to provide them with optimal aesthetics, function and stability for a better quality of life. This review discusses the stages and types of orthodontic treatment in patients with CLP. This article is for-mulated based on a collection of books and published literature. It is recognised that patients with CLP should ideally be treated under the supervision of a multidisciplinary team, starting at the pre/postnatal stage and continuing into adulthood when cranio-facial bone development is complete. It was concluded that the management of CLP care depends on the extent of the cleft de-fect. Patients may experience complex problems related to facial appearance, mastication, airway, hearing and speech. In CLP patients, the malocclusion is related to soft tissue, bone or dental defects, so the orthodontist's role in the timing and sequence of treatment in terms of multidisciplinary team management is essential.